The Procedure of Termination of the Criminal Case (Criminal Prosecution) on Rehabilitation Bases in the Russian Federation and Mongolia - P. V. Kozlovskii; G. Rentsendorj (Сибирское юридическое обозрение, 2019)
The article describes the features of the modern criminal procedure of Mongolia, which consist in the absence of the stage of initiation of criminal proceedings, confluence of a decision of initiation of criminal proceedings and decision about prosecution as an accused, in existence of uniform termination procedure of investigation of the criminal cases subject to termination or referral to court. Comparative legal analysis of rehabilitating grounds for termination of criminal case (criminal prosecution) is carried out. The content of criminal procedural activities at the end of the investigation is considered. The procedure for appealing against decisions on termination of the criminal case is researched. It is characterized by a lack of judicial control in pre-trial proceedings in Mongolia. The procedure and law enforcement practice of realization of the right to rehabilitation is analyzed. The conclusion that departmental regulation hinders its implementation is made. The Authors state that the procedure for termination of the criminal case provided by the Criminal procedure code of Mongolia contains fairly extended guarantees of establishing the truth. The normative regulation completely excludes multiple transfer of the criminal case from the police to prosecutor in the event of discrepancy in the assessment of the qualification of the crime and the completeness of the investigation. The absence of a procedure for the termination of criminal prosecution due to non-involvement is a serious drawback of Mongolian legislation. In general, the mechanism of termination of the criminal case in the criminal procedure legislation of Mongolia is conceptually more consistent and logical, but in terms of elaboration of procedural mechanisms is much inferior to Russian legislation.